Proposing a Theoretical Model to Determine Factors Affecting on Job Satisfaction, Job Performance and Employees Loyalty For Technology Information (IT) Workers - Tran Thi Kim Phuong; Tran Trung Vinh (Bright Institute, 2021)
Information technology (IT) industry in Vietnam has had steady development steps to continuously strengthen its position and role in the sectors such as politics, social - economics, security - defense for further integration into the world. There are many companies now competing in this area. In the unpredictable and competitive business environment, employee plays a vital role for nearly all organizations, thus the important issue is to try to deeply understand work related attitudes and behaviors that affect the well- being of an employee as well as the effective function of an organization. Hence, this paper adapted several previous models in order to find out the influence of workplace environment, pay and promotion potential, fairness and workplace relationship on the level of job satisfaction and examine the relationships among job satisfaction, job performance and employee loyalty for IT workers in Vietnam.